Factors Affecting Generation Z Employee Performance: Analysis of Organizational Culture, Leadership Style and Information Technology - Wasserbauer, Michal; Farhan Saputra (International Journal of Advanced Multidisciplinary, 2024)
The purpose of this study is expected to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of human resource management. The article on factors that influence the performance of generation Z employees: Analysis of corporate culture, leadership style and information technology is a scientific literature article in the scope of human resource management. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or conduct a review of relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from academic online media such as the Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Corporate Culture influences the Performance of Generation Z Employees; 2) Leadership Style influences the Performance of Generation Z Employees; and 3) Information Technology influences the Performance of Generation Z Employees.